Plasma Fibronectin Levels in Clinical Disease States and After Cryoprecipitate Infusion - Ragni, Margaret V; Lewis, Jessica H; Spero, Joel A; Bontempo, Franklin A (Thrombosis and Haemostasis, 1984)
Fibronectin levels were measured in 151 hospitalized patients with liver disease, sepsis, malignancy, leukemia, and following trauma or surgery, using heterologous precipitating antibody in an immunoassay. The mean ( ± S.E.M.) in 25 controls was 0.95 ±0.06 U/ml, with females, 0.83 ± 0.07 U/ml, lower than males, 1.09 ± 0.09 U/ml. Mean fibronectin levels were decreased in all disease groups except in obstructive liver disease. The reduced levels in hepatocellular disease and the restoration of levels to normal after orthotopic liver transplantation in patients with hepatocellular disease supports the theory that hepatic synthesis contributes significantly to plasma fibronectin levels. Following cryoprecipitate infusion in four hemophiliac patients, plasma fibronectin levels rose to 32% to 45% of the levels predicted. In patients with reduced fibronectin and poor clinical response to standard treatment (antibiotics, chemotherapy), cryoprecipitate infusions may raise the levels of fibronectin and, perhaps, contribute to clinical improvement.
Keywords: Fibronectin; Cryoprecipitate; Liver disease